2005
DOI: 10.1007/s10163-004-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of sorbents prepared from ash (waste material) for sulfur dioxide (SO2) removal

Abstract: Sorbents synthesized from various types of ash (coal fly ash, coal bottom ash, oil palm ash, and incinerator ash) for flue gas desulfurization were investigated. The sorbents were prepared by mixing the ashes with calcium oxide and calcium sulfate using the water hydration method. The effects of various sorbent preparation variables, such as the hydration period, the ratio of calcium oxide to ash, and the amount of calcium sulfate, on the Brunauer-EmmettTeller (BET)-specific surface area of the resulting sorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
(22 reference statements)
0
22
0
2
Order By: Relevance
“…The mesopore is believed to responsible for the increased surface area. All the pore radii were within the range of 2-100 nm which as reported in literature [11,14] has been found to be the effective zone for sulphation reaction of SO 2 and Ca(OH) 2 /fly ash sorbents. Higher hydration period and low CaO/fly ash ratio sorbents showed higher BJH volume.…”
Section: Bet Specific Surface Areamentioning
confidence: 72%
See 3 more Smart Citations
“…The mesopore is believed to responsible for the increased surface area. All the pore radii were within the range of 2-100 nm which as reported in literature [11,14] has been found to be the effective zone for sulphation reaction of SO 2 and Ca(OH) 2 /fly ash sorbents. Higher hydration period and low CaO/fly ash ratio sorbents showed higher BJH volume.…”
Section: Bet Specific Surface Areamentioning
confidence: 72%
“…In the presence of water during the hydration process, the active silica and alumina in the siliceous material (in this case fly ash) reacts with hydrated lime to form complex compounds of calcium silicate/ alluminate hydrate [5,9,15,16]. It is believed that it is the complex compounds which are responsible for increased surface area in the sorbent [11]. The high specific surface area is important for the accessibility of Ca 2+ ions by SO 2 in the flue gas.…”
Section: Xrd Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…From the above results, it can be concluded that the ability of FA to capture SO2 is mainly related to its surface area, pore structures and calcium ion content. Specific surface area is increased after the FA is hydrated, leading to more calcium ions that can react with SO2 to produce CaSO4 [149,150].…”
Section: Sulfur Dioxidementioning
confidence: 99%